The Impact of Design Team Characteristics on Construction Project Performance with the Mediating Role of Construction Project Costs - Parisa Khorashadi Moghaddam; Nasrin Izadian; Mehdi Haghighatjoo; Amirhossein Moghaddas Jafari; Marzieh Zahedi (Tehnički Glasnik)
The aim of this research was to examine the impact of design team characteristics on construction project performance with the mediating role of construction project costs. A total of 212 project managers from construction projects participated in the study. Data were collected using a questionnaire and analyzed by PLS-SEM using SMARTPLS3 software. The results indicated that design team characteristics significantly and positively influence the performance of construction projects. Design team characteristics also have a significant and negative impact on construction project costs. The effect of construction project costs on construction project performance was found to be negative and significant. Furthermore, the mediating role of construction project costs in the relationship between design team characteristics and construction project performance was positive and significant. As a result, it can be inferred that the characteristics of the design team in construction projects lead to improved performance of these projects by reducing construction project costs.